Supervisi Kepala Sekolah Dalam Meningkatkan Kinerja Guru Pendidikan Agama Islam Pada Sekolah Dasar Islam Terpadu Di Kecamatan Siak Hulu Kabupaten Kampar - Syafri Syafri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This study aims to determine: (1) Supervision of school principals in improving the performance of Islamic Religious Education teachers, (2) Performance of Islamic Religious Education teachers, and (3) factors that support and hinder the implementation of school principal supervision in Siak Hulu District, Kampar Regency. This research uses descriptive qualitative method. The research was conducted at SDIT in Siak Hulu District, Kampar Regency. The research subject is the principal. The research informants were the teachers of Islamic Religious Education. Data collection techniques using the method of observation, interviews and documentation. Testing the validity of the data obtained using triangulation of sources and methods. The data analysis technique used interactive model analysis, namely data reduction, data presentation and conclusion. The results showed that: (1) The supervision of the principal was running well, but the results were not optimal. The implementation of supervision includes 1) Preparation which includes: (a) preparing instruments, (b) preparation of supervision schedules, (c) informing Islamic Religious Education teachers, and (d) asking learning materials to PAI teachers before conducting supervision. 2) the implementation of supervision which includes: (a) classroom observations, (b) supervision is carried out periodically, (c) supervision is carried out using class visit techniques, and (d) supervision is carried out using individual speaker techniques. 3) Follow-up and Evaluation which includes: (a) providing feedback to teachers who have been supervised, and (b) evaluating supervision. (2) The results of the increase in the performance of Islamic Religious Education teachers have gone quite well. This is evident from the fact that the Islamic Religious Education teacher has done several things including (a) the teacher has made and compiled learning tools, (b) the teacher is able to create PAIKEM learning, (c) the teacher brings lesson plans when teaching, and (d) the teacher evaluates after teaching and learning process activities. 3) factors that support and hinder the supervision of the principal. (1) Supporting factors include: (a) professional competence of supervisors, (b) professional teachers, (c) conducive environment, and (d) support from madrasa citizens, government and society. (2) Inhibiting factors include: (a) aspects of the educational bureaucratic structure and (b) cultural aspects.